PERBANDINGAN PENINGKATAN KADAR GLUKOSA DARAH PUASA SEBELUM DAN SESUDAH PEMBERIAN MADU HUTAN DAN GULA PASIR MAHASISWA ANGKATAN 2015 FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - FANDY NOVRIAN; SITI HAJAR (LP2MTBM MAKARIOZ, 2020)
At the highest levels increase after consuming food. While fasting gold content is the gold content obtained after the patientfasts for 8-10 hours. Carbohydrates that have a low glycemic index cause a slight increase in blood sugar levels, whilecarbohydrates with a high glycemic index will cause a high increase in blood glucose. Honey has a low glycemic index.To determine the increase in the amount of reserves after the honey and granulated forest in the 15th in the 2015 studentforce FK UMSU who fasts for 8 hours. This study used the True Experiment method by designing